New Polymorphs of 2D Indium Selenide with Enhanced Electronic Properties. (9th June 2020) - Sun, Yuanhui; Li, Yawen; Li, Tianshu; Biswas, Koushik; Patanè, Amalia; Zhang, Lijun
Abstract: The 2D semiconductor indium selenide (InSe) has attracted significant interest due its unique electronic band structure, high electron mobility, and wide tunability of its band gap energy achieved by varying the layer thickness. All these features make 2D InSe a potential candidate for advanced electronic and optoelectronic applications. Here, the discovery of new polymorphs of InSe with enhanced electronic properties is reported. Using a global structure search that combines artificial swarm intelligence with first‐principles energetic calculations, polymorphs that consist of a centrosymmetric monolayer belonging to the point group D 3 d are identified, distinct from well‐known polymorphs based on the D 3 h monolayers that lack inversion symmetry. The new polymorphs are thermodynamically and kinetically stable, and exhibit a wider optical spectral response and larger electron mobilities compared to the known polymorphs. Opportunities to synthesize these newly discovered polymorphs and viable routes to identify them by X‐ray diffraction, Raman spectroscopy, and second harmonic generation experiments are discussed. Abstract : New polymorphs of 2D semiconductor indium selenide, which consist of the monolayer with different symmetry, are discovered by artificial intelligence‐based computational material design. The new polymorphs are thermodynamically and kinetically stable, and exhibit a wider optical spectral response and larger electron mobilities compared to the known polymorphs.